2020
DOI: 10.3390/agronomy10101529
|View full text |Cite
|
Sign up to set email alerts
|

Grafting onto an Appropriate Rootstock Reduces the Impact on Yield and Quality of Controlled Deficit Irrigated Pepper Crops

Abstract: In this study, hybrid pepper rootstock NIBER® is tested for its ability to overcome water stress situations under soil conditions. The impact of deficit irrigation (DI) on yield and fruit quality, irrigation water use efficiency is evaluated, and consequently, the agronomic impact of employing water-stress tolerant rootstock is compared to ungrafted pepper plants. For this purpose, plants of the California-type sweet pepper ‘Maestral F1’ grafted onto NIBER® underwent a sustained DI regime during seasons 2018 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Regarding the agronomical parameters studied herein, we have demonstrated that NIBER ® (N) rootstock, previously classified as tolerant to salt and water stresses [19,24], improved commercial production, as well as reduced the non-commercial production when compared to self-grafted (V/V) or V/A6 and V/A8 plants under sub-optimal Ca concentration (SCC) (Figure 1). It is a positive effect of N rootstock given that a low Ca concentration could have resulted in an increase of BER [25,26].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Regarding the agronomical parameters studied herein, we have demonstrated that NIBER ® (N) rootstock, previously classified as tolerant to salt and water stresses [19,24], improved commercial production, as well as reduced the non-commercial production when compared to self-grafted (V/V) or V/A6 and V/A8 plants under sub-optimal Ca concentration (SCC) (Figure 1). It is a positive effect of N rootstock given that a low Ca concentration could have resulted in an increase of BER [25,26].…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, plants grafted onto N rootstock also reached the highest biomass, a symptom of its high vigour (Figure 2A) in OCC and SCC conditions. Our previous results [19,24] using N as rootstock have demonstrated a higher root length under control and abiotic stress indicating that this rootstock could help absorb a larger amount of water and nutrients. Similar studies have also demonstrated that grafting improves production under low nutrient availability, such as in the case of [27], where authors demonstrated that grafting cotton onto a tolerant rootstock improved HI, biomass and K + uptake under low K + concentration.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous studies found that some drought-resistant pepper, watermelon, and tomato rootstocks could alleviate the negative effects on roots and improve their water use efficiency to increase yields under limited irrigation conditions ( Poudyal et al., 2017 ; Al-Harbi et al., 2018 ; Yavuz et al., 2020 ). Thus, the less the reduction of photosynthetic ability, the higher the yield in grafted vegetables ( López-Marín et al., 2017 ; Gisbert-Mullor et al., 2020 ).…”
Section: Crop Yield and Qualitymentioning
confidence: 99%